A Mg-MOF-loaded aerogel material, a preparation method thereof, and application in formaldehyde removal

CN119075952BActive Publication Date: 2025-01-28SHANGHAI HOPE TREE BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411578101.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-28
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

In existing technologies, traditional adsorption materials such as activated carbon have low porosity and insufficient adsorption capacity, MOF materials are not easy to form and their powder properties limit large-scale use, while aerogels lack selectivity for formaldehyde adsorption. Therefore, there is an urgent need to develop efficient methods for formaldehyde removal.

Method used

By generating Mg-MOF in situ in cellulose aerogel, specific adsorption is achieved by utilizing the electrostatic attraction between the unsaturated metal sites of Mg-MOF and the carbonyl groups of formaldehyde.

Benefits of technology

This solves the problem of difficult molding of MOF materials, while achieving efficient formaldehyde adsorption, specifically removing formaldehyde, and improving the performance of adsorption materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119075952B_ABST
    Figure CN119075952B_ABST
Patent Text Reader

Abstract

The present invention discloses an aerogel material loaded with Mg-MOF, a preparation method thereof and an application in formaldehyde removal, wherein the aerogel material loaded with Mg-MOF has a loose and porous structure with a large number of rod-shaped MOFs exposed on the surface. The present invention generates Mg-MOF in situ in cellulose aerogel and achieves efficient formaldehyde removal through specific adsorption of Mg-MOF.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of formaldehyde removal, and relates to an aerogel material loaded with Mg-MOF, a preparation method thereof, and application of the aerogel material in formaldehyde removal. Background Art

[0002] Formaldehyde is a strong carcinogenic compound. Due to its wide application, there is an urgent need for an effective method to remove formaldehyde. At present, most methods for removing formaldehyde use adsorption. Although adsorption can quickly remove formaldehyde from the air, traditional adsorption materials such as activated carbon have problems such as poor porosity and low adsorption capacity. Metal-organic framework materials (MOF) have shown broad application prospects in the field of gas adsorption and separation in recent years due to their advantages such as high porosity, large specific surface area, highly adjustable pore size, and diverse structures. However, MOF materials are not easy to form, and the powder properties limit their large-scale use. Aerogel has a highly permeable cylindrical multi-branched nanoporous three-dimensional network structure with high porosity and extremely low density, but it has no selectivity for the adsorption of formaldehyde. Therefore, it is urgent to develop an effective method to remove formaldehyde. Summary of the invention

[0003] In order to overcome the defects of the above-mentioned prior art, the present invention provides an aerogel material loaded with Mg-MOF and a preparation method and application thereof. The present invention generates Mg-MOF in situ in cellulose aerogel and achieves efficient formaldehyde removal effect through specific adsorption of Mg-MOF.

[0004] The present invention provides an aerogel material loaded with Mg-MOF, wherein the structure of the aerogel material loaded with Mg-MOF presents a loose and porous appearance, and a large number of rod-shaped MOFs are exposed on the surface.

[0005] The Mg-MOF-loaded aerogel material of the present invention generates electrostatic attraction between the unsaturated metal site Mg in the MOF and the carbonyl group of formaldehyde, thereby specifically adsorbing formaldehyde.

[0006] The present invention also provides a method for preparing an aerogel material loaded with Mg-MOF, the method comprising the following steps:

[0007] (1) dispersing nanocellulose in a first solvent, adding a crosslinking agent and a catalyst, stirring at room temperature, centrifuging and washing after the reaction is completed, and freeze-drying to obtain a nanocellulose aerogel;

[0008] (2) dissolving 0.1-10 mol / L magnesium nitrate in a second solvent, and adding the nanocellulose aerogel prepared in step (1) to immerse the aerogel;

[0009] (3) dissolving 4,4′-dioxybiphenyl-3,3′-dicarboxylic acid in a third solvent, dripping the solution into the immersed solution, heating the solution for the first time, taking out the aerogel after cooling to room temperature, and immersing the aerogel in methanol with a volume fraction of 5-30% of 1-(2-aminoethyl)piperidine, and heating the solution for the second time;

[0010] (4) The obtained aerogel is freeze-dried to obtain cellulose aerogel loaded with Mg-MOF.

[0011] In step (1), the first solvent is selected from DMSO.

[0012] In step (1), the mass concentration of the nanocellulose is 0.5-5%; preferably, 1%.

[0013] In step (1), the cross-linking agent is one or more of 1,4-butanediol diglycidyl ether, 1,2,3,4-butanetetracarboxylic acid, etc.; preferably, it is 1,4-butanediol diglycidyl ether.

[0014] In step (1), the mass ratio of the crosslinking agent to the nanocellulose is 1:1-5:1; preferably, it is 1:1.

[0015] In step (1), the mass ratio of the nanocellulose to the catalyst is 1000:1-3000:1; preferably, it is 2000:1.

[0016] In step (1), the catalyst is ScCl4.

[0017] In step (1), the stirring time is 1 h.

[0018] In step (1), the centrifugal washing is performed 3 times.

[0019] In step (2), the second solvent is selected from one of DMF, methanol, DMF / methanol mixed solution, etc.; preferably, it is DMF / methanol mixed solution.

[0020] The volume ratio of DMF to methanol in the DMF / methanol mixed solution is 55:45.

[0021] In step (2), the immersion time is 0.5-3 hours; preferably, 1 hour.

[0022] In step (3), the third solvent is selected from one of DMF, methanol, DMF / methanol mixed solution, etc.; preferably, it is DMF / methanol mixed solution.

[0023] The volume ratio of DMF to methanol in the DMF / methanol mixed solution is 55:45.

[0024] In step (3), the temperature of the first heating is 100-200°C; preferably, 120°C.

[0025] In step (3), the first heating time is 18-30 hours; preferably, 20 hours.

[0026] In step (3), the immersion time is 12 hours.

[0027] In step (3), the temperature of the second heating is 120-180°C; preferably, 130°C.

[0028] In step (3), the second heating time is 0.5-3 h; preferably, 1 h.

[0029] In step (3), the molar ratio of the 4,4′-dioxybiphenyl-3,3′-dicarboxylic acid to magnesium nitrate is 1:1-5:1; preferably, 1:1.

[0030] In step (4), the freeze-drying condition is -50°C.

[0031] The technical difficulty / difficulty that needs to be overcome in the process of in-situ generation of Mg-MOF in cellulose aerogel of the present invention is: how to grow and fix MOF on the surface of the aerogel material while retaining the performance of MOF.

[0032] In a specific embodiment, the preparation of the Mg-MOF-loaded aerogel material of the present invention comprises the following steps:

[0033] (1) Disperse an appropriate amount of nanocellulose in DMSO, add a crosslinker and 0.1uL of catalyst ScCl4, and stir at room temperature for 1h. After the reaction, centrifuge and wash three times, and freeze-dry to obtain nanocellulose aerogel.

[0034] (2) Dissolve 0.1-10 mol / L magnesium nitrate in a DMF / methanol mixed solution (v:v=55:45), add 2 g of the prepared nanocellulose aerogel and immerse for 1 h.

[0035] (3) 4,4′-dioxybiphenyl-3,3′-dicarboxylic acid was dissolved in a DMF / methanol mixed solution (v:v=55:45), and the solution was added dropwise to the above-mentioned magnesium nitrate solution.

[0036] (4) Heat the mixture in an oil bath at 120°C for 20 h.

[0037] (5) After cooling to room temperature, the aerogel was taken out and washed three times with DMF and methanol respectively.

[0038] (6) Under N2 atmosphere, the cleaned aerogel was immersed in methanol with a volume fraction of 5-30% 1-(2-aminoethyl)piperidine for 12 h and then heated at 130 °C for 1 h.

[0039] (7) The obtained aerogel was washed three times with methanol and freeze-dried again to obtain Mg-MOF-loaded cellulose aerogel.

[0040] The possible technical principle involved in the method of the present invention is that a large number of hydroxyl groups on the surface of cellulose can react with Mg 2+ Forming bonds, thereby helping to grow MOFs on the surface of cellulose aerogels.

[0041] The present invention also provides an aerogel material loaded with Mg-MOF prepared by the above method.

[0042] The present invention also provides application of the Mg-MOF aerogel material in formaldehyde removal.

[0043] The beneficial effects of the present invention are as follows: compared with the prior art, the present invention in situ grows rod-shaped MOF on the surface of cellulose aerogel, thereby solving the problem that MOF powder is difficult to form. At the same time, the unsaturated metal site Mg in the MOF exposed on the surface generates electrostatic attraction with the carbonyl group of formaldehyde, thereby specifically adsorbing formaldehyde. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 XRD diagram of cellulose aerogel loaded with Mg-MOF prepared in Examples 1-5 of the present invention;

[0045] Figure 2 The SEM images of aerogels prepared in Examples 1-5 of the present invention and Comparative Example 1;

[0046] Figure 3 The magnified SEM images of the aerogel surfaces prepared in Examples 1-5 of the present invention and Comparative Example 1;

[0047] Figure 4 The formaldehyde removal rate diagram of the aerogels prepared in Examples 1-5 of the present invention and Comparative Example 1;

[0048] Figure 5 The formaldehyde adsorption and nitrogen adsorption curves of the aerogels prepared in Examples 1-5 of the present invention and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0049] The present invention is further described in detail with reference to the following specific examples and drawings. The process, conditions, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art and are not particularly limited by the present invention.

[0050] The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not as limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0052] Example 1

[0053] (1) Disperse nanocellulose at a final concentration of 0.5% (mass ratio) in DMSO, add 1,4-butanediol diglycidyl ether at a final concentration of 0.5% (mass ratio) and catalyst ScCl4 at a final concentration of 0.0005% (mass ratio), and stir at room temperature for 1 hour. After the reaction is completed, centrifuge and wash three times, and freeze-dry to obtain nanocellulose aerogel.

[0054] (2) Dissolve 0.1 mol / L magnesium nitrate in a DMF / methanol mixed solution (v:v = 55:45), add 2 g of the prepared nanocellulose aerogel and immerse for 1 h.

[0055] (3) Dissolve 0.2 mol / L 4,4′-dioxybiphenyl-3,3′-dicarboxylic acid in a DMF / methanol mixed solution (v:v=55:45) and drip it into the above immersed solution.

[0056] (4) Heat the mixture in an oil bath at 120°C for 20 h.

[0057] (5) After cooling to room temperature, the aerogel was taken out and washed three times with DMF and methanol respectively.

[0058] (6) Under N2 atmosphere, the cleaned aerogel was immersed in 5% by volume 1-(2-aminoethyl)piperidine in methanol for 12 h and then heated at 130 °C for 1 h.

[0059] (7) The obtained aerogel was washed three times with methanol and freeze-dried again to obtain Mg-MOF-loaded cellulose aerogel.

[0060] Example 2

[0061] (1) Disperse nanocellulose at a final concentration of 1% (mass ratio) in DMSO, add 1,4-butanediol diglycidyl ether at a final concentration of 1% (mass ratio) and catalyst ScCl4 at a final concentration of 0.001% (mass ratio), and stir at room temperature for 1 hour. After the reaction is completed, centrifuge and wash three times, and freeze-dry to obtain nanocellulose aerogel.

[0062] (2) Dissolve 1 mol / L magnesium nitrate in a DMF / methanol mixed solution (v:v = 55:45), add 2 g of the prepared nanocellulose aerogel and immerse it for 1 h.

[0063] (3) Dissolve 4 mol / L 4,4′-dioxybiphenyl-3,3′-dicarboxylic acid in a DMF / methanol mixed solution (v:v=55:45) and drip it into the above-mentioned immersed solution.

[0064] (4) Heat the mixture in an oil bath at 120°C for 20 h.

[0065] (5) After cooling to room temperature, the aerogel was taken out and washed three times with DMF and methanol respectively.

[0066] (6) Under N2 atmosphere, the cleaned aerogel was immersed in 10% by volume 1-(2-aminoethyl)piperidine in methanol for 12 h and then heated at 130 °C for 1 h.

[0067] (7) The obtained aerogel was washed three times with methanol and freeze-dried again to obtain Mg-MOF-loaded cellulose aerogel.

[0068] Example 3

[0069] (1) Disperse nanocellulose at a final concentration of 2% (mass ratio) in DMSO, add 1,2,3,4-butanetetracarboxylic acid at a final concentration of 4% (mass ratio) and catalyst ScCl4 at a final concentration of 0.001% (mass ratio), and stir at room temperature for 1 h. After the reaction, centrifuge and wash three times, and freeze-dry to obtain nanocellulose aerogel.

[0070] (2) Dissolve 5 mol / L magnesium nitrate in a DMF / methanol mixed solution (v:v = 55:45), add 2 g of the prepared nanocellulose aerogel and immerse it for 1 h.

[0071] (3) Dissolve 50 mol / L 4,4′-dioxybiphenyl-3,3′-dicarboxylic acid in a DMF / methanol mixed solution (v:v=55:45) and drip it into the above immersed solution.

[0072] (4) Heat the mixture in an oil bath at 120°C for 20 h.

[0073] (5) After cooling to room temperature, the aerogel was taken out and washed three times with DMF and methanol respectively.

[0074] (6) Under N2 atmosphere, the cleaned aerogel was immersed in 20% by volume 1-(2-aminoethyl)piperidine in methanol for 12 h and then heated at 130 °C for 1 h.

[0075] (7) The obtained aerogel was washed three times with methanol and freeze-dried again to obtain Mg-MOF-loaded cellulose aerogel.

[0076] Example 4

[0077] (1) Disperse nanocellulose at a final concentration of 5% (mass ratio) in DMSO, add 1,2,3,4-butanetetracarboxylic acid at a final concentration of 20% (mass ratio) and catalyst ScCl4 at a final concentration of 0.002% (mass ratio), and stir at room temperature for 1 h. After the reaction, centrifuge and wash three times, and freeze-dry to obtain nanocellulose aerogel.

[0078] (2) Dissolve 10 mol / L magnesium nitrate in a DMF / methanol mixed solution (v:v = 55:45), add 2 g of the prepared nanocellulose aerogel and immerse it for 1 h.

[0079] (3) Dissolve 50 mol / L 4,4′-dioxybiphenyl-3,3′-dicarboxylic acid in a DMF / methanol mixed solution (v:v=55:45) and drip it into the above immersed solution.

[0080] (4) Heat the mixture in an oil bath at 120°C for 20 h.

[0081] (5) After cooling to room temperature, the aerogel was taken out and washed three times with DMF and methanol respectively.

[0082] (6) Under N2 atmosphere, the cleaned aerogel was immersed in 20% by volume 1-(2-aminoethyl)piperidine in methanol for 12 h and then heated at 130 °C for 1 h.

[0083] (7) The obtained aerogel was washed three times with methanol and freeze-dried again to obtain Mg-MOF-loaded cellulose aerogel.

[0084] Example 5

[0085] (1) Disperse nanocellulose at a final concentration of 5% (mass ratio) in DMSO, add 1,2,3,4-butanetetracarboxylic acid at a final concentration of 15% (mass ratio) and catalyst ScCl4 at a final concentration of 0.005% (mass ratio), and stir at room temperature for 1 hour. After the reaction, centrifuge and wash three times, and freeze-dry to obtain nanocellulose aerogel.

[0086] (2) Dissolve 10 mol / L magnesium nitrate in a DMF / methanol mixed solution (v:v = 55:45), add 2 g of the prepared nanocellulose aerogel and immerse it for 1 h.

[0087] (3) Dissolve 30 mol / L 4,4′-dioxybiphenyl-3,3′-dicarboxylic acid in a DMF / methanol mixed solution (v:v=55:45) and drip it into the above immersed solution.

[0088] (4) Heat the mixture in an oil bath at 120°C for 20 h.

[0089] (5) After cooling to room temperature, the aerogel was taken out and washed three times with DMF and methanol respectively.

[0090] (6) Under N2 atmosphere, the cleaned aerogel was immersed in 30% by volume 1-(2-aminoethyl)piperidine in methanol for 12 h and then heated at 130 °C for 1 h.

[0091] (7) The obtained aerogel was washed three times with methanol and freeze-dried again to obtain Mg-MOF-loaded cellulose aerogel.

[0092] Comparative Example 1

[0093] Nanocellulose with a final concentration of 0.5% (mass ratio) was dispersed in DMSO, 1,4-butanediol diglycidyl ether with a final concentration of 0.5% (mass ratio) and catalyst ScCl4 with a final concentration of 0.0005% (mass ratio) were added, and stirred at room temperature for 1 hour. After the reaction, the mixture was centrifuged and washed three times, and freeze-dried to obtain nanocellulose aerogel.

[0094] Experimental results of Examples 1-5 and Comparative Example 1:

[0095] (1) XRD experiment: XRD confirmed that MOF was successfully prepared in Examples 1-5 of the present invention. Figure 1 .

[0096] (2) SEM: Through SEM, it can be observed that the aerogels prepared in Examples 1-5 of the present invention and Comparative Example 1 all have porous loose structures, as shown in FIG. Figure 2 .

[0097] (3) Further observation shows that there are a large number of rod-like structures on the surface of the aerogels in Examples 1-5 of the present invention, which are the synthesized Mg-MOF. The surface of the control example 1 is smooth. Figure 3 .

[0098] Example 6 Formaldehyde and nitrogen adsorption experiment

[0099] Formaldehyde adsorption experiment: The formaldehyde removal experiment was carried out in a 200L sealed cabin. The heating table was preheated to 80°C, 150ul of formaldehyde solution was dropped into a glass culture dish and placed on the heating table for 30 minutes to completely volatilize the formaldehyde, then 10g of aerogel sample was placed in it, and the atmospheric sampler was used to sample at different time points and record the values. The results are shown in Figure 1. Figure 4 As shown in the figure, compared with the blank group without aerogel, Examples 1-5 of the present invention can effectively remove formaldehyde, and Example 5 of the present invention can remove 99% of formaldehyde within 24 hours. However, Control Example 1 can only remove 20% of formaldehyde. Figure 4 .

[0100] Furthermore, the adsorption experiment confirmed that the aerogel materials prepared in Examples 1-5 of the present invention had a good adsorption effect on formaldehyde, and a general adsorption effect on nitrogen which existed in large quantities in the air. Figure 5 .

[0101] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0102] As used in the present invention, the term "comprising" is an open expression, that is, including the contents specified in the present invention but not excluding other contents.

[0103] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.

[0104] Although the embodiments of the present description have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present description, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an aerogel material loaded with Mg-MOF, characterized in that: The method comprises the following steps: (1) dispersing nanocellulose in a first solvent, adding a crosslinking agent and a catalyst, stirring at room temperature, centrifuging and washing after the reaction is completed, and freeze-drying to obtain nanocellulose aerogel; the catalyst is ScCl4; the crosslinking agent is one or two of 1,4-butanediol diglycidyl ether and 1,2,3,4-butanetetracarboxylic acid; (2) dissolving 0.1-10 mol / L magnesium nitrate in a second solvent, and adding the nanocellulose aerogel prepared in step (1) to immerse the aerogel; (3) dissolving 4,4′-dioxybiphenyl-3,3′-dicarboxylic acid in a third solvent, dripping the solution into the immersed solution, heating the solution for the first time, taking out the aerogel after cooling to room temperature, and immersing the aerogel in methanol with a volume fraction of 5-30% of 1-(2-aminoethyl)piperidine, and heating the solution for the second time; (4) The obtained aerogel is freeze-dried to obtain cellulose aerogel loaded with Mg-MOF.

2. The method according to claim 1, characterized in that In step (1), the mass concentration of the nanocellulose is 0.5-5%; and the first solvent is selected from DMSO.

3. The method according to claim 1, characterized in that In step (1), the mass ratio of the crosslinking agent to the nanocellulose is 1:1-5:1; the mass ratio of the nanocellulose to the catalyst is 1000:1-3000:1; the stirring time is 1 hour; and the number of centrifugal washing is 3 times.

4. The method according to claim 1, characterized in that In step (2), the second solvent is selected from one of DMF, methanol, and a DMF / methanol mixed solution; and the immersion time is 0.5-3 hours.

5. The method according to claim 1, characterized in that In step (3), the third solvent is selected from one of DMF, methanol, and a DMF / methanol mixed solution; the temperature of the first heating is 100-200° C.; the time of the first heating is 18-30 hours; and the immersion time is 12 hours.

6. The method according to claim 4 or 5, characterized in that The volume ratio of DMF to methanol in the DMF / methanol mixed solution is 55:

45.

7. The method according to claim 1, characterized in that In step (3), the temperature of the second heating is 120-180° C.; the time of the second heating is 0.5-3 h; and the molar ratio of the 4,4′-dioxybiphenyl-3,3′-dicarboxylic acid to magnesium nitrate is 1:1-5:

1.

8. An aerogel material loaded with Mg-MOF prepared by the method according to any one of claims 1 to 7.

9. Use of the Mg-MOF-loaded aerogel material as claimed in claim 8 in formaldehyde removal.